INOVASI PROGRAM SIAP MELAYANI MASYARAKAT MALAM HARI (SIMMAMAH) DI KECAMATAN TAMAN, SIDOARJO - Andyansah, Ronaldo Rendra; Meirinawati, Meirinawati (Universitas Negeri Surabaya, 2023)
Taman Subdistrict, Sidoarjo has launched an evening service called Simmamah Program. Unfortunately, there are still challenges in implementing this program in Taman Subdistrict, Sidoarjo. The purpose of this research is to describe and analyze the Innovation of the Ready to Serve the Night Community Program (Simmamah) in Taman Sub-district, Sidoarjo. The research type in this thesis is qualitative with a descriptive approach. The theory used in this research is based on Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Republik Indonesia Nomor 91 Tahun 2021 Pasal 3 tentang pembinaan inovasi pelayanan pubik. The respondents in this research were selected using purposive sampling technique, which consisted of the Subdistrict Head of Taman, Secretary of Taman Subdistrict, Head of the Subdivision of Population Administration of Taman Subdistrict, Simmamah Program population administration service employee in Taman District, Community as users of the Simmamah Program. This research employs data collection techniques consisting of observation, interviews, and documentation. The data analysis techniques in this study consist of data collection, data reduction, data presentation, and conclusion making. The research findings in this article indicate that the innovation of the Simmamah Program in Taman Subdistrict, Sidoarjo has met the aspect of novelty. Furthermore, the implemented innovation has proven to be effective, However, the program has not fully met the aspect of usefulness due to several challenges, such as unfriendly communication by the staff with the residents dan lack of specific notification regarding the results of the product, particularly in the processing of ID cards (KTP). The aspect of easy dissemination in the Simmamah Program is well-established which can be proven through several urban village that have implemented the evening service system as in Taman Subdistrict, Sidoarjo. The Simmamah Program has received support from various factors, such as facilities, budget, and support from sub-district employees, thus fulfilling the aspect of sustainability.